Fluxos de conhecimento em subsidiárias de corporações multinacionais: uma survey de empresas no Brasil - Lessa Neto, Antonio Thomaz Pacheco (2013)
Knowledge flows, especially in subsidiaries of multinational corporations, now have an increasing importance in organizations and therefore the discussion of research in the field. The aim of this work is to analyze flows not only through transfers, but also conversions of knowledge between the three families of intangible assets (external structure, internal structure and individual competence), since, for the creation of value, the key lies in the fact that such transfers and conversions be effective (SVEIBY, 2001). Concerning the method, this dissertation presents an empirical study through a survey applied along the Brazilian subsidiaries of multinational corporations, from a theoretical construct Knowledge-based view (KBV) where makes an analysis of the assets of individual competence, internal structure and external structure, and having for its object of study brazilian companies in Brazil listed in data collection known as the best and biggest from business magazine EXAME covering the year 2012. The study indicates, for the sample data (nine respondents) removed of the universe effectively researched (140 companies and not the initial 565), that there is the maximization of value creation from knowledge flows in two directions only by knowledge transfers and conversions of Individual Competencies for External Structure, within the Internal Structure, of Internal Structure for Individual Competencies and within the External Structure